Elemental concentration in deposited dust on urban tree leaves depending applied washing method - Molnár, Vanda (Acta Geographica Debrecina Landscape & Environment series, 2016)
In our study, the concentrations of elements were determined in leaves and deposited dust of Quercus robur and Celtis occidentalis which were washed with distilled water, rainwater and tap water. According to our results, each washing solutions had a significant effect on the elemental concentrations in the foliage dust. The highest concentrations of aluminum, chromium, copper, iron, manganese and zinc were detected in the foliage dust which was washed down with rainwater. The highest strontium and barium concentrations were found in the foliage dust which was washed down with tap water. We observed chromium and manganese accumulation in Q. robur leaves, while the concentrations of barium, copper and strontium were the highest in C. occidentalis leaves. Our results demonstrated the effect of rainwater on tree leaves which phenomenon occurs naturally. Rainwater may wash down the dry deposited foliage dust from the leaf surface, but it also delivers a certain concentration of elements through wet deposition.